Pengaruh Kepuasan Kerja dan Motivasi Kerja Terhadap Kinerja Dosen di Fakultas Ekonomi dan Bisnis Universitas Islam Sumatera Utara - Nalsution, Lizal Salfiral; Wahyuni, Neni Sri; Julkarnain, Julkarnain; Syafrizal, Syafrizal (Universitas Medan Area, 2025)
This study aims to determine the effect of job satisfaction and work motivation on the performance of lecturers at the Faculty of Economics and Business, Islamic University of North Sumatra. The population in this study was all lecturers' performance at the Faculty of Economics and Business, Islamic University of North Sumatra, totaling 50 people and sampling was carried out using census sampling so that 50 people were used as samples. This research method uses quantitative. The data analysis technique used in this study is multiple linear regression. The results of the study indicate that job satisfaction has a positive and significant effect on the performance of lecturers at the Faculty of Economics and Business, Islamic University of North Sumatra, work motivation has a positive and significant effect on the performance of lecturers at the Faculty of Economics and Business, Islamic University of North Sumatra, and job satisfaction and work motivation have a positive and significant effect on the performance of lecturers at the Faculty of Economics and Business, Islamic University of North Sumatra.